Protocol for live-cell super-resolution imaging of transport of pre-ribosomal subunits through the nuclear pore complex - Mark Tingey; Samuel L. Junod; Coby Rush; Weidong Yang (STAR Protocols, 2024)
Summary: Here, we present a protocol for single-molecule super-resolution imaging of the nuclear export of pre-ribosomal subunits pre-40S and pre-60S through nuclear pore complexes. We describe steps for plating cells and co-transfecting cells. We then detail steps for using single-point edge-excitation sub-diffraction microscopy, allowing visualization of real-time dynamics of the pre-ribosomal subunits.For complete details on the use and execution of this protocol, please refer to Junod et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.